BENTUK PENGIKAT JAMINAN DAN PENYELESAIAN KREDIT MACET DI LEMBAGA PERKREDITAN DESA (LPD) CANGGU DI KABUPATEN BADUNG - Ardi Artha Prabawa, Bagus Gede; Wiryawan, I Wayan; Rudy, Dewa Gde (Kertha Negara : Journal Ilmu Hukum, 2013)
Village Credit Institutions (LPD) is a financial institutionengaged in the financial sector in a traditional village, which serves asone institution of saving financial and delivering loan from society tosociety in a village. In loan terms LPD sets a guaranteed loan ascollateral for the repayment of loans since the loan given to borrowersare not always in large amount but there are also some in smallamounts. Credit guarantees can be in the form of moving objects suchas vehicles and immovable objects such as land and buildings.Utilization of LPD aimed at improving living standards of ruralcommunities to support rural development. LPD activity was not muchdifferent from the activities of banks or other financial institutions.
Keywords: Rural Credit Institutions (LPD), Suppliers Credit, Villagers, Credit guarantee